Immunosuppressive and metabolic agents that influence allo‐ and xenograft survival by in vivo expansion of T regulatory cells. (6th September 2020) - Zhao, Yanli; Hu, Wenjun; Chen, Pengfei; Cao, Mengtao; Zhang, Yingwei; Zeng, Changchun; Hara, Hidetaka; Cooper, David K. C.; Mou, Lisha; Luan, Shaodong; Gao, Hanchao
Abstract: The transplanted organs or cells survive if the recipient receives adequate long‐term immunosuppressive therapy. Immunosuppressive therapy combined with cell‐based strategies (eg, regulatory T cell [Treg]‐based therapy) promotes graft survival. A combination of Treg‐based therapy and minimal or no immunosuppressive drug therapy would have the potential to minimize the risks of the complications and side effects of these drugs. Fortunately, some immunosuppressive and other agents not only impede the effector T cell response, but also help generate new CD4 + Tregs from conventional effector T cells. These agents include IL‐2, TGF‐β, agents that block the CD40/CD40L costimulation pathway, mTOR inhibitors, and histone deacetylase inhibitors. Consequently, a state of relative unresponsiveness to the transplanted organ may be induced through the expansion of Tregs. We here review the effect of these various agents on expansion of CD4 + Tregs in allo‐ and xenotransplantation. The expansion of Tregs might allow a dose reduction of the standard immunosuppressive drugs.